2021
DOI: 10.2106/jbjs.rvw.20.00243
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Hemiarthroplasty with Nonprosthetic Glenoid Arthroplasty

Abstract: Glenoid component wear and loosening are the principal failure modes of anatomic total shoulder arthroplasty (aTSA).The ream-and-run (RnR) procedure is an alternative glenohumeral arthroplasty for patients who wish to avoid the risks and limitations of a prosthetic glenoid component.During the RnR procedure, the arthritic glenoid is conservatively reamed to a single concavity, while the prosthetic humeral component and soft tissues are balanced to provide both mobility and stability of the joint.The success of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Getz et al reported a revision rate of 25% at a mean of 2.7 years 25 . We believe, consistent with Matsen et al, that patient selection and expectations are important factors for achieving a successful outcome after RnR 22 . Patients treated with RnR may benefit from avoiding long-term glenoid loosening and failure, which was reported to result in a glenoid revision rate of 29% at 20 years 8 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Getz et al reported a revision rate of 25% at a mean of 2.7 years 25 . We believe, consistent with Matsen et al, that patient selection and expectations are important factors for achieving a successful outcome after RnR 22 . Patients treated with RnR may benefit from avoiding long-term glenoid loosening and failure, which was reported to result in a glenoid revision rate of 29% at 20 years 8 .…”
Section: Discussionsupporting
confidence: 90%
“…Proposed advantages include the preservation of glenoid bone stock and a lack of postoperative activity restrictions related to the glenoid compared with aTSA. Several reports, many by Matsen and colleagues, document excellent outcomes [18][19][20][21][22][23][24] . Other groups have reported more limited experiences.…”
mentioning
confidence: 99%
“…The so-called ream and run technique has previously been reported in which the glenoid is reamed without being resurfaced with a polyethylene component. Although not the best option for all patients, there have been good results reported 13,14 . This technique has been used in patients with dysplastic glenoid, glenoid morphology not amenable to resurfacing, and in cases of glenoid fracture preventing stable insertion of a glenoid component.…”
Section: Discussionmentioning
confidence: 99%
“…The ream-and-run procedure combines HA with concentric spherical glenoid reaming to correct glenoid articular surface incongruity in order to recenter the humeral head and create durable glenoid articulation without implant or graft [46][47][48][49][50][51][52][53]. The procedure provides an alternative to TSA using a conventional all-polyethylene glenoid implant.…”
Section: Discussionmentioning
confidence: 99%